Experimental Study of Earthquake Simulator for 3D Cold-Formed Steel Frame Structure - Alemdar, Fatih; Al-Gaadi, Fuad Mohammed Ahmed (LATIN AMER J SOLIDS STRUCTURES, 2022)
This paper aims to perform the experimental test and numerical FE analysis of the cold-formed steel frame structure to provide new proposals to improve the strength, rotation capacity, and seismic energy dissipation in these structures. A 3D full-scale three-story CFS frame structure is experimentally investigated under four sets of input data for 100% and 50% scales of Northridge and Kocaeli earthquake acceleration records using the shaking table test. In each test, the frame acceleration and displacement are observed. A FE model is employed to assert the validity of the experimental test. The results indicated that the maximum story drift ratio of the frame ranges from 1.14% to 3.70%. It is observed that the average similarity ratio of the maximum displacement results between FE analysis and shaking table test is 92%. It is shown that the translational stiffness for the system decrease as the earthquake acceleration records decrease. It is also shown that using the image processing technique in the shaking table test can offer much more acceptable and economical solutions in determining the displacement parameters.
Keywords: Numerical simulation of CFS frame structures; Finite Element seismic analysis; Lightweight steel frame structures; Shaking table experiment; SEISMIC RESPONSE; PERFORMANCE; BEHAVIOR; JOINT; Engineering; Mechanics